A Cross-sectional study to assess the Diabetes-Related Distress in Patients undergoing therapy at a specialized healthcare facility - Sai Vignesh, Challa Venkata; Rao, V.R.Mohan; Sree, Kolli Laasya; Chevuri, Mounika; Aishwariyaa, Vinayak Mani (Journal of Neonatal Surgery, 2025)
Background: Diabetes mellitus is a long-term condition that necessitates ongoing medical attention, self-management by the patient, and adjustments to lifestyle habits. Alongside its physical complications, diabetes often leads to significant psychological stress, known as diabetes-related distress, which impacts treatment adherence and quality of life. Objective: The research is focused to analyse the prevalence of Diabetes related distress in Type 2 Diabetes Mellitus Patients and also to evaluate the correlation between Diabetes Distress and glycemic control (HbA1c) Methods: A sample of adult T2DM patients aged more than 18years from the outpatient and inpatient departments of Chettinad Hospital and Research Institute, Chennai, were assessed. Patients with psychiatric illnesses, those on psychotropic drugs or corticosteroids, and those with other severe medical ailments requiring immediate intervention were excluded. Results: The research revealed a significant occurrence of diabetes-related distress among the participants, influenced by various sociodemographic and clinical factors that affect the levels of distress. Key factors associated with increased distress included poor glycemic control, longer duration of diabetes, and lack of family support. Conclusion: The findings emphasize the need for routine screening and early intervention for diabetes distress to improve management outcomes. Comprehensive care models that integrate psychological support into diabetes management are essential for addressing the emotional well-being of diabetic patients and enhancing treatment adherence..